Hungarian Parallels to the Anecdotal Style of Švejk - Gintli, Tibor (Slavia Centralis, 2020)
This study examines the parallels between 20th-century Hungarian anecdotal narration and the narrative of Švejk. First, the genre components of Švejk are examined in order to confirm the presence and function of anecdotal characteristics. The anecdotal elements of works by the Hungarian writer Józsi Jenő Tersánszky (The Story of a Pencil, the Kakuk Marci novels, The Legend of the Rabbit Stew) are then compared to Hašek’s methods.
Keywords: anecdotal novel; oral narration; episodic structure; satire; worm’s-eye view